Musculoskeletal disorders in upper limbs in dental students: exposure level to risk factors - Patrícia Petromilli Nordi Sasso Garcia; Camila Pinelli; Juliana dos Reis Derceli; Juliana Álvares Duarte Bonini Campos (Universidade Estadual de Campinas, 2015)
Aim: This study assessed the risk factors of undergraduate students to develop musculoskeletal disorders (MSD) in the upper limbs, regarding gender, type of dental clinical procedure, mouth region treated, and the four-handed dentistry practice. Methods: Dental students enrolled in the 8th semester in the Araraquara School of Dentistry, UNESP, Brazil, were photographed while practicing 283 dental procedures. The Rapid Upper Limb Assessment (RULA) method was used to evaluate the working postures of each student. The photographs were evaluated and a final risk score was attributed to each analyzed procedure. The prevalence of risk factors of developing MSD was estimated by point and by 95% confidence interval. The association between the risk factor of developing disorders and variables of interest were assessed by the chi-square test with a significance level of 5%. Results: The risk factors of developing MSD were high, regarding most dental procedures performed by the undergraduate students (score 5: 7.07%, CI95%: 4.08- 10.06%; score 6: 62.54%, CI95%: 56.90-68.18%). There was no significant association between the RULA final score and gender (p=0.559), and type of dental procedure (p=0.205), and mouth regions by arch (p=0.110) or hemi-arch (p=0.560), and the use of four-handed dentistry (p=0.366). Conclusions: It can be concluded that gender, type of dental clinical procedure, mouth region treated, and practice of four-handed dentistry did not influence the risk of developing MSD in the upper limbs among the dental students evaluated; however, they are at a high risk of developing such disorders.